E-Wallet and Food Consumption: Satisfaction and Loyalty Of Gen Z College Student - Anak Agung Istri Arundhati Aiswara; Ketut Budi Susrusa; Gede Mekse Korri Arisena; Ary Bakhtiar (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2025)
The increasing use of e-wallets among college student, particularly for food purchases, faces challenges such as unstable digital payment infrastructure and limited platform features. This study aims to identify e-wallet usage frequency, assess consumer satisfaction and loyalty, and explore the relationship between these factors. Utilizing a literature review method, the research involves planning, conducting, and reporting on existing scholarly works related to the topic. Findings indicate user characteristics and e-wallet usage frequency significantly influence college student' satisfaction and loyalty. The research concludes that security, convenience, service quality, and promotional effectiveness are crucial in shaping college student satisfaction and loyalty toward e-wallets. To improve user adoption and retention, e-wallet providers should enhance security measures, ensure efficient service, and offer appealing promotions like cashback and discounts. Furthermore, incorporating financial education and budget management features, along with additional services such as transportation and bill payments, can increase the relevance and utility of e-wallets for Gen Z college student.